ANALISIS PENGARUH PERSEPSI WISATAWAN TERHADAP REVISIT INTENTION DI MUSEUM WAYANG KOTA TUA, JAKARTA BARAT - Felix Agustian; Dewanta Facrureza (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was conducted at the Jakarta Wayang Museum with the aim of analyzing whether tourists’ perceptions affect their intention to revisit. The research used a descriptive quantitative approach, with data collected through questionnaires distributed to 100 respondents who had visited the museum. Respondents were selected using purposive sampling and the data were analyzed with the assistance of SPSS software. Based on the analysis results, it was found that the perception variable simultaneously affects the intention to revisit, accounting for 72.8% of the influence. The dimensions contributing to perception include the 7A tourism components: Attraction, Accessibility, Amenity, Ancillary, Activities, Available Package, and Awareness. This study recommends improving management strategies that are more relevant to current attractions and package availability. The findings are expected to serve as input for the development of sustainable cultural tourism destination management that aligns with the characteristics of the current generation.